A Randomized Trial of Mentored vs Nonmentored Military Medics Compared in the Application of a Wound Clamp Without Prior Training: When to Shut Up and Just Watch!. (19th February 2020) - Kirkpatrick, Andrew W; Mckee, Jessica L; Netzer, Itamar; Mckee, Ian A; McBeth, Paul; Wachs, Juan P; Ball, Chad G; Glassberg, Elon
ABSTRACT: Introduction: Hemorrhage control is a basic task required of first responders and typically requires technical interventions during stressful circumstances. Remote telementoring (RTM) utilizes information technology to guide inexperienced providers, but when this is useful remains undefined. Methods: Military medics were randomized to mentoring or not from an experienced subject matter expert during the application of a wound clamp (WC) to a simulated bleed. Inexperienced, nonmentored medics were given a 30-second safety briefing; mentored medics were not. Objective outcomes were time to task completion and success in arresting simulated bleeding. Results: Thirty-three medics participated (16 mentored and 17 nonmentored). All (100%) successfully applies the WC to arrest the simulated hemorrhage. RTM significantly slowed hemorrhage control ( P  = 0.000) between the mentored (40.4 ± 12.0 seconds) and nonmentored (15.2 ± 10.3 seconds) groups. On posttask questionnaire, all medics subjectively rated the difficulty of the wound clamping as 1.7/10 (10 being extremely hard). Discussion: WC application appeared to be an easily acquired technique that was effective in controlling simulated extremity exsanguination, such that RTM while feasible did not improve outcomes. Limitations were the lack of true stress and using simulation for the task. Future research should focus on determining when RTM is useful and when it is not required.